Genetic and structural analysis of a virulence determinant in polyomavirus VP1. - Bauer, P H (1995)
The LID strain of polyomavirus differs from other laboratory strains in causing a rapidly lethal infection of newborn C3H/Bi mice. This virulent behavior of LID was attenuated by dilution, yet at sublethal doses LID was able to induce tumors at a high frequency, like its parent virus PTA. By constructing and assaying LID-PTA recombinant viruses and by DNA sequencing, the determinant of virulence in LID was mapped to the major viral capsid protein, VP1. The VP1s of LID and PTA differed at two positions: at 185, LID has phenylalanine and PTA has tyrosine, and at 296, LID has alanine and PTA has valine. Results obtained with viruses constructed by site-directed mutagenesis showed that alanine at position 296 is sufficient to confer a fully virulent phenotype regardless of which amino acid is at position 185. However, with valine at position 296, an effect of phenylalanine at position 185 is apparent, as this virus possesses an intermediate level of virulence. A crystal structure of polyomavirus complexed with 3'-sialyl lactose previously indicated van der Waals contacts between the side chain of valine 296 and the sialic acid ring (T. Stehle, Y. Yan, T. L. Benjamin, and S. C. Harrison, Nature [London] 369:160-163, 1994). When this interaction was modeled with alanine, these contacts were greatly reduced. Direct confirmation that the substitutions in VP1 affected receptor binding was obtained by studying virus hemagglutination behavior. The ensemble of results are discussed in terms of the idea that a lower affinity of the virus for its receptor can result in more rapid spread and increased pathogenicity.